Knowledge about HPV and Screening of Cervical Cancer among Women from the Metropolitan Region of Natal, Brazil. (31st March 2013) - Lima, Érika Galvão; de Lima, Diego Breno Soares; Miranda, Cleine Aglacy Nunes; de Sena Pereira, Valeska Santana; de Azevedo, Jenner Chrystian Veríssimo; de Araújo, Josélio Maria Galvão; de Medeiros Fernandes, Thales Allyrio Araújo; de Azevedo, Paulo Roberto Medeiros; Fernandes, José Veríssimo
Abstract : Objective . The purpose of this study was to assess the knowledge level about HPV and screening of cervical cancer in women from the metropolitan region of Natal, Brazil. Materials and Methods . A descriptive cross-sectional study involving sexually active women was conducted. The participants were submitted to a face-to-face interview, using a structured questionnaire that permitted the quantification of data and opinions of the respondents. Results . Most participants (70.9%) had poor knowledge about HPV and also the Pap test (53.0%). The high level of knowledge about HPV was associated with age, education, marital status, household income, and pregnancy, while the high level of knowledge about the Pap test proved to be associated only with education and household income. Conclusion . The results highlight the need for performing educational campaigns emphasizing the role of HPV in the etiology of cervical lesions of different degrees, including cervical cancer, as well as the importance of having a Pap test regularly to prevent these diseases.